LINGKUNGAN PENDIDIKAN DALAM AL-QUR’AN DAN HADIS - Hasbullah, Hasbullah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
Educational environment is needed in the education process, because the educational environment serves to support the process of teaching and learning, a comfortable environment and support for the implementation of an education is needed. The environment is distinguished into the biological environment, the non-living natural environment, the artificial environment and the social environment. Education is one of the first obligations for parents. In Islam, the person most responsible for the education of the child is the parent. The family is the